CHANGING PSYCHIATRIC MANIFESTATIONS OF NEUROSYPHILIS OVER A PERIOD OF 23 YEARS1 - Narayanan, H. S. (Medknow Publications, 1980)
Cases diagnosed as general paralysis of insane at the psychiatric services of NIMHANS for 23 years from 1955 to 1977 were studied to analyse the trends of age distribution, sex proportion, annual admission rate and clinical categories. It was found that the mean age and the proportion of females did not show any impressive change during these years. Among the clinical categories the simple dementia type showed a considerable rise over the years. The acute confusional type showed a definite decrease during this period. A less impressive but definite decrease was found in the expansive type. Depressive form of GPI found in a considerable proportion of cases earlier has rarely been seen over the last one decade. The schizophrenic type has not shown any significant change. These findings are discussed in comparison with the earlier studies both in India and abroad. The possible causes of these trends are outlined.